2013
DOI: 10.11138/ccmbm/2013.10.1.047
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of cortical and trabecular tissues to bone strength: insights from denosumab studies

Abstract: SummaryAll materials undergo an aging process which is characterized essentially by changes of the rigidity (stiffness), of the ability to absorb the stresses (toughness) and then ultimately in the mechanical resistance (strength). Both cortical and trabecular bone undergo a continuous process of structural remodeling with the main aim to preserve their biomechanical properties. An imbalance in this process, which promotes bone resorption, results in a quantitative loss of bone tissue and in a qualitative alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…In contrast, a low Mg diet did not affect extrinsic biomechanical properties. Cortical components have a prominent role in bone strength [ 27 ], which may explain why a low Mg diet did not affect extrinsic biomechanical properties despite a decrease in trabecular BMD and intrinsic biomechanical properties. In contrast, some approximations were made in calculating bone geometry for mechanical properties, or there could be a measurement sensitivity issue with the whole bone mechanical testing, which may also explain this inconsistency.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a low Mg diet did not affect extrinsic biomechanical properties. Cortical components have a prominent role in bone strength [ 27 ], which may explain why a low Mg diet did not affect extrinsic biomechanical properties despite a decrease in trabecular BMD and intrinsic biomechanical properties. In contrast, some approximations were made in calculating bone geometry for mechanical properties, or there could be a measurement sensitivity issue with the whole bone mechanical testing, which may also explain this inconsistency.…”
Section: Discussionmentioning
confidence: 99%
“…Because BMD is considered only a surrogate measure of bone strength[58], micro-architecture determinants are necessary to evaluate the true impact of a treatment on trabecular bone quality because trabecular bone is more readily lost in the OVX rodent model[59]. Preservation of the trabecular micro-architecture contributes to bone strength and may reduce fracture risk independently of BMD and BMC[60, 61]. We found that CGA27 and CGA45 significantly improved all parameters of trabecular micro-architecture in the femurs of OVX rats.…”
Section: Discussionmentioning
confidence: 99%
“…In one report, denosumab therapy resulted in a significant, early, and sustained increase in bone mineral density (BMD) and enhanced bone strength in the improvement of both cortical and trabecular bones [ 4 ]. Another review described that denosumab treatment for 6 years maintained a low fracture incidence, reduced bone turnover, and an increase in BMD [ 5 ].…”
Section: Introductionmentioning
confidence: 99%